The management information needs of academic Heads Of Department in universities in the United Kingdom - Brendan Loughridge (Information Research: An International Electronic Journal, 1996)
A study of the management information needs of academic Heads of Department in universities, using a Critical Success Factors approach, was conducted in 1994/1995. A sample of sixteen English universities was developed, based principally on age, history, size and the nature and range of academic disciplines represented within them. In each of the selected institutions, the University Librarian (or, in one case, Deputy Librarian) and two or, in some cases, three academic Heads of Department were interviewed, as were a number of senior administrative staff such as Registrars, Secretaries and Finance Officers and the Heads or Directors of more specialised units such as Industrial Development Units.